Postgraduate educational research on violence, gender, and HIV/AIDS in and around schools (1995–2004) - Moletsane, R; Madiya, N (South African Journal of Higher Education, 2011)
Social issues such as HIV/AIDS, bullying, and violence have recently come to the fore in schooling and related research in South Africa. This article describes and critically analyses Masters and Ph.D. research done in education in the period 1995–2004, with particular reference to the voice given to social issues, namely: gender, violence, and HIV/AIDS and their interconnectedness. It explores issues, trends, and patterns in research emerging in the first decade of democracy in South Africa.